2016
DOI: 10.1016/j.cmi.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Strain features and distributions in pneumococci from children with invasive disease before and after 13-valent conjugate vaccine implementation in the USA

Abstract: The effect of second-generation pneumococcal conjugate vaccines on invasive pneumococcal disease (IPD) strain distributions have not yet been well described. We analysed IPD isolates recovered from children aged <5 years through Active Bacterial Core surveillance before (2008–2009; n = 828) and after (2011–2013; n = 600) 13-valent pneumococcal conjugate vaccine (PCV13) implementation. We employed conventional testing, PCR/electrospray ionization mass spectrometry and whole genome sequence (WGS) analysis to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
250
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(265 citation statements)
references
References 29 publications
(84 reference statements)
15
250
0
Order By: Relevance
“…In the present study, the number of cases of serotype 35B IPD increased considerably after the introduction of PCV13, which is consistent with recent reports (6,8). The increase was directly related to the continued clonal expansion of CC558 and the emergence of CC156 among serotype 35B isolates.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present study, the number of cases of serotype 35B IPD increased considerably after the introduction of PCV13, which is consistent with recent reports (6,8). The increase was directly related to the continued clonal expansion of CC558 and the emergence of CC156 among serotype 35B isolates.…”
Section: Discussionsupporting
confidence: 81%
“…A study from Canada also identified a serotype 35B isolate that represented an SLV of ST156 (ST9346) in 2011 (25). The two studies reported 1 or 2 occurrences of ST156 or its SLV in association with serotype 35B (8,25). Thus, ST156 did not contribute to the increased prevalence of serotype 35B in those studies.…”
Section: Fig 4 Eburst Analysis Of Penicillin Mic Distribution and Mulmentioning
confidence: 91%
See 1 more Smart Citation
“…35 By 2015, the CDC's Active Bacterial Core Surveillance program showed that serotypes 15B/ C and 35B have emerged as 2 of the top 4 most frequent causes of IPD in children less than 5 years of age. 41 Furthermore, as serotypes 15B/C and 35B emerged, it became clear that many isolates are b-lactam resistant. 36,38,41 Strengths of this study include the prospective collection of a large number of nasopharyngeal samples from a high risk population for pneumococcal isolation.…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, as serotypes 15B/C and 35B emerged, it became clear that many isolates are b-lactam resistant. 36,38,41 Strengths of this study include the prospective collection of a large number of nasopharyngeal samples from a high risk population for pneumococcal isolation. Limitations of this study include the low carriage rates resulting in low number of pneumococci isolated, limiting the generalizability of serotype and antibiotic susceptibility results and factors associate with carriage.…”
Section: Discussionmentioning
confidence: 99%